Sustainability feasibility of fungi-based biocolorants by biotechnological routes - de Oliveira, F. [UNESP]; de Oliveira, A. C.; Sánchez-Muñoz, S.; Balbino, T. R.; Santos-Ebinuma, V. C. [UNESP]; da Silva, S. S. (Elsevier, 2024)
Biotechnological industries based on biorefinery projects are being faced as environmentally clean technologies for the manufacturing of added-value goods such as biocolorants. Aligned with the principles of circular bioeconomy, employing agro-industrial waste as the main feedstock for microbial transformation aligns with the United Nations Sustainable Development Goals. This approach not only facilitates cost-effective production of high-value metabolites but also addresses waste management issues, thereby promoting economic development. However, the potential of fungi-based biocolorants still requires strategic planning to develop enhanced sustainable technologies, validating green approaches over petroleum-based systems. Thus, there is a necessity to analyze the environmental impacts of the biocolorants biorefinery. This review aimed to discuss the production of biocolorants from microbial sources (focusing on carotenoids and polyketides) on a sustainable perspective. A critical evaluation of sustainability aspects based on life cycle assessment was included comprehending information on the recent trends available of biocolorants manufacturing using renewable feedstock to accomplish the advancing of greener bioprocesses. The upcoming challenges in biorefinery development for biocolorants were also discussed.
Keywords: Agro-industrial waste; Biocolorants; Fungi; Life cycle assessment; Sustainability